Lao People's Democratic Republic : Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Lao P.D.R. (IMF Staff Country Reports; Country Report, 2011)
The economic growth of Lao P.D.R. was buoyed by mining and hydropower sectors, garment exports, non-regional tourism, and FDI inflows following the recovery from the global economic crisis. The Bank of Lao P.D.R. (BoL) also raised its overdraft lending rate. Net domestic assets of the BoL continued to expand rapidly net injections of liquidity into the banking system, and an expansion of other assets. Medium-term economic prospects, macroeconomic and financial policies, accelerated structural reforms to diversify the economy, improve the business climate, and foster trade.